2012
DOI: 10.1111/j.1463-1318.2012.03054.x
|View full text |Cite
|
Sign up to set email alerts
|

Is laparoscopic right colectomy more effective than open resection? A meta‐analysis of randomized and nonrandomized studies

Abstract: Laparoscopic-assisted right colectomy results in less blood loss, a shorter length of hospital stay and lower postoperative short-term morbidity compared with ORC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…LTME appears to have clinically and oncologically measurable advantages over OTME in patients with primary resectable rectal cancer in both short term and long term follow ups. The findings of this article are consistent with previously published Cochrane review and a meta-analysis [43,44] . Majority of the studies in the Cochrane review [44] were non-randomized, trials and therefore the conclusion was considered weaker and biased.…”
Section: Anastomosis By Knight-griffen Techniquesupporting
confidence: 82%
See 1 more Smart Citation
“…LTME appears to have clinically and oncologically measurable advantages over OTME in patients with primary resectable rectal cancer in both short term and long term follow ups. The findings of this article are consistent with previously published Cochrane review and a meta-analysis [43,44] . Majority of the studies in the Cochrane review [44] were non-randomized, trials and therefore the conclusion was considered weaker and biased.…”
Section: Anastomosis By Knight-griffen Techniquesupporting
confidence: 82%
“…Majority of the studies in the Cochrane review [44] were non-randomized, trials and therefore the conclusion was considered weaker and biased. Similarly a recently published meta-analysis [43] failed to demonstrate the oncological safety and advantages of LTME over OTME.…”
Section: Anastomosis By Knight-griffen Techniquementioning
confidence: 99%
“…Also, as is usual for laparoscopic colorectal surgery, the operation time is longer than that required for open surgery. This does not diminish the general advantages of laparoscopic colorectal surgery in general and also not in our series, as demonstrated by the shorter hospital stay [9][10][11][12]. Another disadvantage of the procedure is that we need rather a lot of large bore (10 and 12 mm) ports.…”
Section: Discussionmentioning
confidence: 92%
“…This holds true not only for left but also for right hemicolectomy [11,12]. For a long time, right hemicolectomy has been considered to be a beginner's procedure in colorectal surgery because of its low complexity.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, some recent studies have shown that mortality and morbidity were significantly lower after laparoscopic right-sided colectomy compared to mortality and morbidity after open surgery [12, 13]. …”
Section: Introductionmentioning
confidence: 99%